A mixed-methods process evaluation of Family Navigation implementation for autism spectrum disorder. (July 2019) - Broder-Fingert, Sarabeth; Qin, Sarah; Goupil, Julia; Rosenberg, Jessica; Augustyn, Marilyn; Blum, Nate; Bennett, Amanda; Weitzman, Carol; Guevara, James P; Fenick, Ada; Silverstein, Michael; Feinberg, Emily
There is growing interest in Family Navigation as an approach to improving access to care for children with autism spectrum disorder, yet little data exist on the implementation of Family Navigation. The aim of this study was to identify potential failures in implementing Family Navigation for children with autism spectrum disorder, using a failure modes and effects analysis. This mixed-methods study was set within a randomized controlled trial testing the effectiveness of Family Navigation in reducing the time from screening to diagnosis and treatment for autism spectrum disorder across three states. Using standard failure modes and effects analysis methodology, experts in Family Navigation for autism spectrum disorder (n = 9) rated potential failures in implementation on a 10-point scale in three categories: likelihood of the failure occurring, likelihood of not detecting the failure, and severity of failure. Ratings were then used to create a risk priority number for each failure. The failure modes and effects analysis detected five areas for potential "high priority" failures in implementation: (1) setting up community-based services, (2) initial family meeting, (3) training, (4) fidelity monitoring, and (5) attending testing appointments. Reasons for failure included families not receptive, scheduling, and insufficient training time. The process with the highest risk profile was "setting up community-based services." Failure in "attending testing appointment" was rated as the most severe potential failure. A number of potential failures in Family Navigation implementation—along with strategies for mitigation—were identified. These data can guide those working to implement Family Navigation for children with autism spectrum disorder.